Interview with Mohammad Tajuddin Khan, president of the Andhra Pradesh Civil Liberties Committee Hydrabad, on Naxalite movement in Andhra Pradesh, interviewed by Kabir and Majumdar - Kabir, Shahriar.
Interview with Mohammad Tajuddin Khan, president of the Andhra Pradesh Civil Liberties Committee Hydrabad, on Naxalite movement in Andhra Pradesh, interviewed by Kabir and Majumdar.